2019
DOI: 10.1017/s1478951519000610
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in patients with cancer: A systematic review of prevalence, risk factors, intervention and assessment

Abstract: ObjectivesSuicidal ideation (SI) underlies risk of death by suicide. It is well established that patients with cancer are at increased risk of death by suicide. Therefore, understanding SI in patients with cancer is critically important. The goal of this systematic review was to investigate the prevalence, risk factors, intervention, and assessment of SI in patients with cancer.MethodsThis systematic review was registered with the PROSPERO database (CRD42018115405) and was guided by the PRISMA statement. We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 75 publications
(200 reference statements)
5
63
0
1
Order By: Relevance
“…A recent review reported a wider range of percentages between 0.8 and 71.4% of suicidal ideation in cancer patients, compared to a range of 1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].8% in the general population (11). Another review, involving 44 relevant studies indicated that the prevalence of suicidal ideation ranged from 0.8 to 46.2% among cancer patients; with lowest figures being reported by an American study while the highest percentage was reported in Chinese samples (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review reported a wider range of percentages between 0.8 and 71.4% of suicidal ideation in cancer patients, compared to a range of 1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].8% in the general population (11). Another review, involving 44 relevant studies indicated that the prevalence of suicidal ideation ranged from 0.8 to 46.2% among cancer patients; with lowest figures being reported by an American study while the highest percentage was reported in Chinese samples (12).…”
Section: Introductionmentioning
confidence: 99%
“…For example, advanced cancer stage, impaired physical functioning, cancer pain, depression, anxiety, hopelessness, existential distress, and limited social support were consistently proven to be risk factors for suicidal ideation in cancer patients (11). Gender, age, race, and treatment type were also reported to be associated with suicidal ideation, however, the findings have been often conflictive (12). A recent Chinese study reported that depression, anxiety, metastatic cancer, poor performance status, surgery, and palliative care were significantly associated with suicidal ideation, whereas, compared to demographic or clinical factors, psychological characteristics were more vital in predicting patient's suicidal ideation (13).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the articles took place in a multi‐step process, following the example of Kolva et al. (2019). Firstly, the researchers (JS, JCC) independently reviewed titles and abstracts of the retrieved literature fully blinded, labelling them with “Yes,” “No” or “Maybe” for a full‐text review, based on the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Previous systematic reviews in this field focused on the broad topic of suicide, researching incidence rates for suicide in patients with cancer, risk factors or potential screening tools (Anguiano, Mayer, Piven, & Rosenstein, 2012; Robson et al., 2010; Spoletini et al., 2011). SI in individuals with cancer has been reviewed as well (Kolva, Hoffecker, & Cox‐Martin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Even when patients are screened "positive," the complete picture of difficulties and impairments that are likely to ac-company moderate to severe depressive symptoms is not clear. Research with other cancer types would suggest that there are cooccurring stressors and cognitive and behavioral disruptors, and they too may impede cancer patients' coping with the diagnosis and decision-making as do depressive symptoms [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%